Polish-Studies Relationship Between Julije Benešić and Zdenka Marković - Batinić, Ana (Poznańskie Studia Slawistyczne, 2015)
Being a private form of communication, personal letters are usually not written to be published. The act of their publication, therefore, may be considered as somewhat voyeuristic. However, since the authors of the correspondence in this contribution – Julije Benešić and Zdenka Marković – are two public figures of great importance not only in Croatian literary and cultural context, but also in the promotion of Croatian Polish studies as well as intercultural relations between Croatia and Poland in the first half of the twentieth century, we believe that its printing is justified. Their correspondence may be considered as an interesting addition to the facts about their lives and work that can be found in different research papers and books published so far, providing insight in the inner world of thoughts and emotions they shared.